The Role of Local Therapy in The Treatment of Patients with Acute Rhinosinusitis in Outpatient Settings - Yunusova Z.V.; Kasimova N.D. (Zien Journals, 2023)
Acute rhinosinusitis is one of the most common diseases encountered in the practice of an otorhinolaryngologist. The frequency of visits from patients with acute rhinosinusitis is increasing both in outpatient and inpatient practice. Despite the development of modern medicine, the relevance of the problem of this disease is growing every year, and this has a number of reasons. In the first hours and days of the disease, local treatment is very important, which helps to quickly stop inflammation and achieve recovery without the use of systemic antibacterial drugs
Keywords: Local therapy; acute rhinosinusitis; protargol; outpatient treatment